Employment protection legislation, labor courts, and effective firing costs - Juan F. Jimeno; Marta Martínez-Matute; Juan S. Mora-Sanguinetti (IZA Journal of Labor Economics, 2020)
In many countries, labor courts play a central role in the determination of firing costs by monitoring and supervising the procedures for dismissals, and, eventually, deciding severance payments mandated by the employment protection legislation (EPL). To get some insights about the impact of labor courts on effective firing costs, we explore a new database that contains information on labor courts' intervention in firings before and after the implementation of significant EPL reforms modifying severance payments and procedures for dismissals. Our results suggest that labor court rulings on economic dismissals did not fully translate the reduction of firing costs mandated by the new EPL to effective firing costs.
Keywords: J52; J53; K31; K41; 330; employment protection legislation; firing costs; unemployment; labor courts